China-European union relations: A developing geoeconomic axis - Babić Blagoje S. (Međunarodni Problemi)
China and the European Union are very interested in developing their mutual relations. They strengthen their positions in the world business by their co-ordinated acting. In their mutual relations, they apply Geoeconomics’ methods. They do not regard each other as a military threat but as one of the main economic partners. Their economies are highly complementary. “The common economic interests“ have a decisive role in China EU policy and EU China policy, respectively. EU is China’s largest economic partner. It is its largest export market, the largest source of new technologies and equipment and one of the largest sources for foreign investments. China is the second important source of industrial products import to EU and the fastest growing export market for EU. The EU enlargement to the East both favourably and unfavourably affects China’s interests. The main cause of friction in China-EU relations is a high Chinese surplus in their mutual trade, high competitiveness of Chinese products on the EU market and China’s pursuit of energy sources in the parts of the world that Western countries, including the leading EU member states, regard as traditionally “forbidden“ such as the Middle East and Africa. China and EU have created mechanisms to settle conflicts of interest in their mutual trade through dialogue.